Examination of the Usefulness of Figma as a Prototyping Interface Platform on the Learning Outcomes of PJBL-based Informatics in High School - Lakilaki, Eogenie; Artamananda, Artamananda; Akbar, Muhammad; Azhim, Muhammad Fajrul; Abdillah, Muhammad Fayyad (FKIP - Universitas Riau, 2025)
This study aims to examine the effectiveness of using Figma as a prototyping platform in Project-Based Learning (PjBL)-based informatics learning at the senior high school level. Figma, as a cloud-based tool, offers real-time collaboration features that can improve students' interface design skills as well as encourage teamwork. This study uses a quantitative approach with Pearson correlation test, heatmap correlation, correlation matrix and linear regression analysis to analyze the relationship between learning management variables, communication process, student responses, and learning activities to student learning outcomes. The results show that the communication process variable has the most dominant influence on student learning outcomes. This study confirms that the integration of Figma in PjBL-based learning can improve 21st century skills, including critical thinking, creativity, and collaboration, thus preparing students for the challenges of the world of work in the digital era.